Watching plants' dance: movements of live and dead branches linked to atmospheric water demand. Issue 8 (23rd August 2021) - Hallmark, Alesia J.; Maurer, Gregory E.; Pangle, Robert E.; Litvak, Marcy E.
Abstract: Diurnal branch movements in woody plants have only recently been described in detail. While previously only vegetative and reproductive structures have been known to move on hourly timescales, imaging technologies such as terrestrial laser scanning and near‐surface repeat digital photography provide a means of remotely monitoring plant movements at high enough temporal and spatial resolution to capture rhythmic movements of woody material. Virtually, nothing is known about the range of species and ecosystems in which woody movements might occur or what causes these movements. We report that diurnal woody branch movements occur in a number of tree and shrub species across a broad range of abiotic conditions. We examined detailed branch movements in one species, creosote ( Larrea tridentata ), and found that branch movements were highly correlated with humidity, air temperature, vapor pressure deficit, and stem water potential: all factors related to plant water status. We also found that live and dead branch movements were distinct in the timing of their movements and in the abiotic conditions with which they were most correlated. Changes in dead branch position were most correlated with humidity, with these movements consistently lagging 1–2 h behind changes in humidity. Live branch movements were also highly correlated with vapor pressure deficit and humidity but went from lagging 1–2 h behind changes in these abiotic conditions in summer to being nearly in sync in winter. We believe that this is the first study that (1) documents diurnal branch movements in creosote, (2) differentiates between the movements of live and dead branches, and (3) relates environmental data to these movements. We hope these findings encourage other researchers to more closely examine imagery from their sites for evidence of branch movements, which may provide deeper insights into water and solute movements in plants and physiological responses to water stress.